1993
DOI: 10.1246/bcsj.66.892
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Synthetic Method of 1-Alkylazulenes and Azulene by the Reactions of 3-Methoxycarbonyl-2H-cyclohepta[b]furan-2-one with in situ Generated Enamines

Abstract: Methyl 3-alkylazulene-1-carboxylates were synthesized in high yields by the reaction of 3-methoxycarbonyl-2H-cyclohepta[b]furan-2-one with in situ generated morpholine enamines of aldehydes. Treatment of the esters with 100% phosphoric acid gave 1-alkylazulenes in excellent yields. Azulene was also synthesized in a good yield via methyl azulene-1-carboxylate with a modification of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…However, because NIS is a rather expensive reagent, we examined a new iodination procedure using N ‐chlorosuccinimide (NCS) and NaI, to prepare the 1‐iodoazulene derivatives 3 and 4 for the palladium‐catalyzed cross‐coupling reaction 10. The reaction of 1,6‐di‐ tert ‐butylazulene ( 1 )11 and methyl 7‐isopropylazulene‐1‐carboxylate ( 2 )12 with NCS/NaI in acetic acid at room temperature afforded the corresponding 1‐iodoazulene derivatives 3 and 4 in 94 and 96 % yield, respectively (Scheme ). The yields of the products were slightly improved by using this procedure compared with those from the reaction with NIS 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because NIS is a rather expensive reagent, we examined a new iodination procedure using N ‐chlorosuccinimide (NCS) and NaI, to prepare the 1‐iodoazulene derivatives 3 and 4 for the palladium‐catalyzed cross‐coupling reaction 10. The reaction of 1,6‐di‐ tert ‐butylazulene ( 1 )11 and methyl 7‐isopropylazulene‐1‐carboxylate ( 2 )12 with NCS/NaI in acetic acid at room temperature afforded the corresponding 1‐iodoazulene derivatives 3 and 4 in 94 and 96 % yield, respectively (Scheme ). The yields of the products were slightly improved by using this procedure compared with those from the reaction with NIS 8.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of 2-iodoazulene (5) [15] with ethynylferrocene afforded 2-(ferrocenylethynyl)azulene (12) in 96 % yield. Reaction of diethyl 2-chloroazulene-1,3-dicarboxylate (6) with ethynylferrocene afforded 13 in 92 % yield, although aryl chloride is usually less reactive toward the palladiumcatalyzed cross-coupling reaction compared with that of aryl iodide and bromide (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…showed higher TS and PSE values, than [1][2][3][4][5][6][7] and [15][16][17][18][19][20][21]. The most active compound [8][9][10][11][12][13][14] induced apoptosis in C9-22 OSCC cells at 4-times higher CC 50 . Quantitative structure-activity relationship analysis of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] demonstrated that their tumorspecificity was correlated with chemical descriptors that explain the molecular shape and hydrophobicity.…”
Section: Abstract Background/aim: Very Few Studies Of Anticancer Actmentioning
confidence: 99%
“…The most active compound [8][9][10][11][12][13][14] induced apoptosis in C9-22 OSCC cells at 4-times higher CC 50 . Quantitative structure-activity relationship analysis of [1][2][3][4][5][6][7][8][9][10][11][12][13][14] demonstrated that their tumorspecificity was correlated with chemical descriptors that explain the molecular shape and hydrophobicity. Conclusion: 7-Isopropyl-3-methyl-N-propylazulene-1-carboxamide [8] can be a potential candidate of lead compound for manufacturing new anticancer drug.…”
Section: Abstract Background/aim: Very Few Studies Of Anticancer Actmentioning
confidence: 99%
“…First attempts to prepare 2 directly from the diester 30 or its corresponding dicarboxylic acid 35, which is easily obtained by saponification of 30, by established decarboxylation methods of esters (H,PO,: [28]; LiBr in HMPTA: [29]; pyridine in DMF: [30]) and carboxylic acids (CF,SO,H in 1,2-dichloroethane: [31]; Pb(OAc), in pyridine/ MeCN : [32]) failed, since mainly decomposition and polymerization occurred. Therefore, we decided to choose a stepwise degradation of both ester groups.…”
mentioning
confidence: 99%